National character and public spirit in Britain and France, 1750-1914 - Romani, Roberto (Cambridge University Press, 2002)
Romani considers a distinction between 'national character' as a static and stereotype-laden concept, and 'public spirit' as a notion suggesting the necessity of certain qualities to operate free institutions. Many major authors of the period 1750-1914 (like Montesquieu, Voltaire, Hume, Millar, Burke, Tocqueville, Spencer, Hobson and Durkheim) are considered.